2016
DOI: 10.1017/dmp.2016.109
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Domestic Violence Against Pregnant Females After the Great East Japan Earthquake in Miyagi Prefecture: The Japan Environment and Children’s Study

Abstract: Continuous monitoring and support for pregnant females may be necessary to address this issue in disaster-affected areas. (Disaster Med Public Health Preparedness. 2017;11:216-226).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 34 publications
0
38
0
1
Order By: Relevance
“… 40 Similarly in Japan, postearthquake prevalence of physical IPV against pregnant women was significantly higher in affected areas compared with the national prevalence (p < 0.0001) but there was no difference in psychological violence. 48 Meanwhile, hurricane exposure in the USA significantly increased (p = 0.001) reported lifetime IPV prevalence one year (12.5%) and two years (34.4%) postdisaster, but did not change prevalence of sexual violence. 47 …”
Section: Resultsmentioning
confidence: 93%
“… 40 Similarly in Japan, postearthquake prevalence of physical IPV against pregnant women was significantly higher in affected areas compared with the national prevalence (p < 0.0001) but there was no difference in psychological violence. 48 Meanwhile, hurricane exposure in the USA significantly increased (p = 0.001) reported lifetime IPV prevalence one year (12.5%) and two years (34.4%) postdisaster, but did not change prevalence of sexual violence. 47 …”
Section: Resultsmentioning
confidence: 93%
“…[7][8][9] The authors previously reported an increased incidence of perinatal depression and psychological distress in areas affected by the Great East Japan Earthquake. [10][11][12][13] Natural disasters destroy social networks and community relationships. This loss of community also results in secondary emotional trauma and depression.…”
mentioning
confidence: 99%
“…Stress and an increase in alcohol consumption were considered to be other environmental factors that impacted cleft birth prevalence after Hurricane Katrina (Goenjian et al, 2011). Increases in stress, including post-traumatic stress disorder, depression, and sleep disturbance, were also reported in Miyagi Prefecture after the 2011 Tō hoku earthquake and tsunami (Fujihara et al, 2012;Fushimi, 2012;Tuerk et al, 2013;Kinoshita and Woolley, 2015;Onose et al, 2015;Sakuma et al, 2015;Fujiwara et al, 2017;Sakurai et al, 2017;Xu et al, 2018;Yabe et al, 2018;Inoue et al, 2017). Some reports described deteriorating liver function due to an increase in alcohol consumption (Nakanishi et al, 2014;Murakami et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Electric cables and water supply structures were catastrophically damaged, resulting in a severely deteriorated quality of life. There have been many reports regarding the disaster's impact on human health, including physical (Nakano et al, 2012;Itabashi et al, 2014;Sakurai et al, 2016;Hayashi et al, 2017;Sado et al, 2018) and psychological problems (Fujihara et al, 2012;Fushimi, 2012;Tuerk et al, 2013;Kinoshita and Woolley, 2015;Onose et al, 2015;Sakuma et al, 2015;Fujiwara et al, 2017;Sakurai et al, 2017;Xu et al, 2018;Yabe et al, 2018;Inoue et al, 2017). The impact on regional birth outcomes has also been studied; it has been reported that the incidences of preterm birth and low birth weight were not adversely affected by the disaster (Sugawara et al, 2018).…”
Section: Introductionmentioning
confidence: 99%